Socio-epistemic analysis of scientific knowledge production in little science research - Alberto Pepe (tripleC: Communication, Capitalism & Critique)
The processes that drive knowledge production and dissemination in scientific environments are embedded within the social, technical, cultural and epistemic practices of the constituent research communities. This article presents a methodology to unpack specific social and epistemic dimensions of scientific knowledge production using, as a case study,  the Center for Embedded Networked Sensing (CENS), a National Science Foundation “little science” research center involved in theoretical and applied work in the field of wireless communication and sensor networks. By analysis of its scholarly record, I construct a social network of coauthorship, linking individuals that have coauthored scholarly artifacts (journal articles and conference papers), and an epistemic network of topic co-occurrence, linking concepts and knowledge constructs in the same scholarly artifacts. This article reports on ongoing work directed at the study of the emergence and evolution of these networks of scientific interaction. I present some preliminary results and introduce a socio-epistemic method for an historical analysis of network co-evolution. I outline a research design to support further investigations of knowledge production in scientific circles.